(untitled) (Педагогіка вищої та середньої школи, 2022)
The system of the creative tasks using of traditional and untraditional methods of teaching (method of improvisation, method of association, and others) at the fourth stage of formation of the pupils’ readiness to Creative activity is considered in the article.